12th INTERNATIONAL CERAMICS CONGRESS PART J 2010
DOI: 10.4028/www.scientific.net/ast.71.86
|View full text |Cite
|
Sign up to set email alerts
|

Si-C-O Fibres in Gas Reactive Atmospheres

Abstract: The aim of the present work was to investigate the high temperature reaction between Si- C-O fibres and Cl2, and to correlate the carbon layer growth kinetics with their initial composition and structure. Large disparities have been observed between the various materials reaction rates. If a large amount of mixed silicon atom environments increases the reactivity of Si-O-C materials with Cl2, this sole feature does not explain all the experimental results. Traces of heteroelements (Ti, Zr, Al…) or percolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…4(a)). The chlorination behavior of SiOC materials observed in the present study are well consistent with the Brisebourg et al [51] in which the authors showed that mixed SiC x O 4Àx environments in silicon oxycarbide tend to destabilize the structure and enhance the Si-sites chlorination. In that sense, the pore size in the residual C is probably related to the SiC x O 4Àx (0 < x < 4) domain size from which it originates.…”
Section: Structure Of Sioc-cdcsupporting
confidence: 93%
“…4(a)). The chlorination behavior of SiOC materials observed in the present study are well consistent with the Brisebourg et al [51] in which the authors showed that mixed SiC x O 4Àx environments in silicon oxycarbide tend to destabilize the structure and enhance the Si-sites chlorination. In that sense, the pore size in the residual C is probably related to the SiC x O 4Àx (0 < x < 4) domain size from which it originates.…”
Section: Structure Of Sioc-cdcsupporting
confidence: 93%